2003
DOI: 10.4049/jimmunol.171.4.1994
|View full text |Cite
|
Sign up to set email alerts
|

Nramp1 Functionality Increases Inducible Nitric Oxide Synthase Transcription Via Stimulation of IFN Regulatory Factor 1 Expression

Abstract: Natural-resistance associated macrophage protein 1 (Nramp1) encodes a transmembrane phagolysosomal protein exerting resistance toward infections with intracellular pathogens by a mechanism not fully elucidated so far. We used the murine macrophage cell line RAW264.7, stably transfected with functional (RAW-37) or nonfunctional (RAW-21) Nramp1, to study for differences in the expression of NO, a central antimicrobial effector molecule of macrophages. Following stimulation with IFN-γ and LPS, Nramp1-expressing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 42 publications
2
66
1
Order By: Relevance
“…2 In this regard, it is interesting to mention a recent study describing upregulation of iNOS by NRAMP1 that is associated with increased expression of interferon regulatory factor 1 and augmented binding affinity to the iNOS promoter. 18 In conclusion, our current observations suggest that M. bovis infection promotes the expression of NRAMP1 and iNOS by bovine MØs. Evidence that this expression is particularly strong in the granuloma suggests that these molecules are involved in the host defense against mycobacteria in cattle TB.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…2 In this regard, it is interesting to mention a recent study describing upregulation of iNOS by NRAMP1 that is associated with increased expression of interferon regulatory factor 1 and augmented binding affinity to the iNOS promoter. 18 In conclusion, our current observations suggest that M. bovis infection promotes the expression of NRAMP1 and iNOS by bovine MØs. Evidence that this expression is particularly strong in the granuloma suggests that these molecules are involved in the host defense against mycobacteria in cattle TB.…”
Section: Discussionmentioning
confidence: 60%
“…3,4,35 In a recent study we demonstrated high expression of NRAMP1 in granulomas of M. bovis-infected cattle; 15 since granulomas are protective inflammatory reactions, 17,20,21 it was thought that NRAMP1 plays a defensive role against mycobacteria locally. This finding, in addition to recent studies showing a regulatory role for NRAMP1 in iNOS production, 2,18 prompted this study, which aims to analyze the expression of NRAMP1 and iNOS in M. bovis-infected cattle. In addition, we analyzed nitrotyrosine (NT) expression as an indication of iNOS enzymatic activity and NO production.…”
mentioning
confidence: 99%
“…The following oligonucleotides were used: NF-B sense, 5Ј-AGCTTCA-GAGGGGACTTTCCGAGAGG-3Ј and NF-B, antisense 5Ј-TCGACCTCTCGGAAAGTCCCCTCTGA-3Ј. Gel mobilityshift assay and supershift assays were performed as described (13). For supershift assays, 1 g of the appropriate anti-NF-B subunit antibody (p50, p65; Santa Cruz Biotechnology) was added.…”
Section: Methodsmentioning
confidence: 99%
“…Slc11a1 is pleiotropic, interfering with macrophage activation, 17 oxidative and nitrosamine bursts, 18 TNFa, IFNg, and IL-1 production, 19 and the expression of MHC class II molecules. 20,21 The mutation corresponding to the Slc11a1 S allele determines a gly169asp substitution resulting in a nonfunctional protein 22 that promotes an accumulation of ions inside the phagosome that favors pathogen replication.…”
mentioning
confidence: 99%